STRUKTUR KOMUNITAS BIVALVIA DI KAWASAN MANGROVE DESA TANAH MERAH KABUPATEN KEPULAUAN MERANTI UNTUK RANCANGAN HANDOUT SEBAGAI BAHAN AJAR BIOLOGI KELAS X - Mimi Mirahika; Suwondo Suwondo; Elya Febrita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research was conducted in May - June 2022 with the aim of knowing the bivalve community structure in the mangrove area of Tanah Merah Village for the design of handouts as biology teaching materials for class X. This research was carried out in the mangrove area of Tanah Merah Village for bivalve sampling while for identification of bivalves carried out at the Laboratory of the Biology Education Study Program, PMIPA FKIP Department, Riau University. The parameters measured in this study were species composition, abundance, diversity, dominance, temperature, salinity, pH, sediment type, and organic matter. The research method used was a survey method, where sampling samples used the squared transect method. At the study site, 3 (three) observation stations were determined, three transects were drawn at each station, where each transect was placed in a 5m x 5m square plot. Based on the research results, 3 species of bivalves were found, namely Anadara granosa Phapia textile, and Geloma erosa. Bivalve abundance values obtained between stations ranged from 0.57-0.89 ind/m2. The index value of species diversity ranges from 0.68-1.51, which is classified as moderate and the dominance index value ranges from 0.37-0.71. The results of the study can be used as an alternative teaching material in the form of handouts in class X high school biology learning.Key Word : Bivalve, Handout, Structure Community